Factors That Influence the Clinical Implementation of Aerobic Exercise in Stroke Rehabilitation: A Theory-Informed Qualitative Study. - Inness, Elizabeth L; Jagroop, David; Andreoli, Angie; Bayley, Mark; Biasin, Louis; Danells, Cynthia; Hall, Jayne; Mansfield, Avril; McDonald, Alison; Nishri, Diane; Salbach, Nancy M; Taylor, Denise; et al. (PTJ: Physical Therapy & Rehabilitation Journal, 2022)
Objective Best practice guidelines recommend that aerobic exercise (AEx) be implemented as early as possible poststroke, yet the prescription of AEx remains limited in stroke rehabilitation settings. This study used theoretical frameworks to obtain an in-depth understanding of barriers and enablers to AEx implementation in the stroke rehabilitation setting. Methods A qualitative, descriptive study was conducted. Participants were recruited from 4 stroke rehabilitation settings in Ontario, Canada, that have participated in an implementation study to provide structured AEx programming as part of standard care. Six clinician focus groups (with 19 physical therapists and 5 rehabilitation assistants) and one-to-one interviews with 7 managers and 1 physician were conducted to explore barriers and enablers to AEx implementation. The Theoretical Domains Framework and Consolidated Framework for Implementation Research informed content analysis for clinician and manager perspectives, respectively. Results Barriers specific to resource constraints and health care system pressures, combined with patient goals, led to interventions to improve function being prioritized over AEx. Successful implementation was enabled through an interprofessional approach and team engagement in the planning and implementation process. Health care providers described concerns about patient safety, but confidence and capability for implementing AEx were enabled by education, skill development, use of exercise tests, and consultation with individuals with content expertise. Participants described the development of supportive processes that enabled AEx implementation within team workflows and shared resources. Conclusion Strategies to support implementation of AEx in stroke rehabilitation should incorporate knowledge and skills, the provision of clinical decision-making tools, access to expert consultation, the roles and social influence of the interprofessional team and formal and informal leaders, and supportive processes adapted to the local context. Impact Results from this study will inform the development of a clinical implementation toolkit to support clinical uptake of AEx in the stroke rehabilitation setting.